The Tamrau Block of NW New Guinea records late Miocene–Pliocene collision at the northern tip of the Australian Plate. (1st August 2019) - Webb, Max; White, Lloyd T.; Jost, Benjamin M.; Tiranda, Herwin
Highlights: We present a revised stratigraphy for the Tamrau Block of NW New Guinea. This block records the Cenozoic geological history of the northern tip of Australia. An island arc collided with the Tamrau Block in the Late Miocene–Pliocene. This caused uplift and the present-day topography of NW New Guinea. Detrital zircons indicate the Tamrau Block is allochthonous. Abstract: The Tamrau Block is a geological terrane located in the Bird's Head Peninsula of NW New Guinea. Relatively little is known about this terrane and how it relates to other parts of western New Guinea. The geological history and provenance of this terrane is difficult to resolve because it is found at the boundary between the Australian, Philippine Sea, Caroline, and Pacific plates. This segment of the plate boundary records episodes of deformation, magmatism, and exhumation associated with the interaction of these three tectonic plates. For instance, the southern edge of the Tamrau Block is bounded by a major strike-slip fault zone (the Sorong Fault Zone), previous studies imply that the terrane may have been translated some distance along this fault zone during the Cenozoic. We seek to understand the geological history and provenance of the Tamrau Block. To do this, we report new field observations made during a three-month field campaign in a poorly exposed region, together with new petrographic and geochronology data. U–Pb detrital zircon age spectra were obtained from five sedimentary and metamorphic sequences and the results were combined with existing biostratigraphic age data to reassess the stratigraphy and tectonic history of the region. The oldest rocks in the Tamrau Block (the Tamrau Formation) represent Jurassic–Cretaceous passive margin sediments. These were deformed and metamorphosed in at least three distinct events – the first phase of which involved amphibolite facies conditions (and produced the first reported instance of metamorphic kyanite from the Bird's Head), possibly in the Oligo–Miocene. These Jurassic–Cretaceous rocks are unconformably overlain by the Ajai Limestone. Both units are cross-cut and overlain by intrusives and eruptives of the middle Miocene Moon Volcanics. The heat associated with these intrusives baked the Tamrau Formation and the overlying Ajai Limestone, resulting in andalusite growth in the Tamrau Formation and hornfelsing of the limestones. Deposition of the overlying Koor Formation occurred from the middle–late Miocene, and was partially contemporaneous with volcanism. An episode of crustal shortening occurred after the deposition of the Koor Formation with the development of asymmetric folds and steeply-inclined reverse faults. This is marked by a late Miocene–Pliocene break in deposition between the Koor Formation and undeformed Opmorai Formation (∼10.5–4.5 Ma) and records the collision of part of an oceanic island arc (Tosem Block) to the Tamrau Block, an event also recognised in other parts of New Guinea. A comparison of the U–Pb detrital zircon age spectra from sedimentary rocks within the Tamrau Block and those reported in other studies indicate that there is no relationship between the rocks of the Tamrau and Kemum blocks (which are in faulted contact). Instead, the U–Pb detrital age data share similarities with rocks from the Lengguru Fold and Thrust Belt and Weyland Overthrust in the south-east. We therefore propose that the Tamrau Block was transported westwards ∼300 km to its current position along the Sorong Fault Zone after the late Miocene–Pliocene collision between the Tosem Block and the northern margin of the Australian Plate.